POLEMIK PROGRAM TANAH SISTEMATIS LENGKAP (PTSL) DALAM SENGKETA KEPEMILIKAN TANAH STUDI KASUS: DESA TAMBELANG KECAMATAN KRUCIL KABUPATEN PROBOLINGGO - Ahmad Mubaraq; Husni Mubaroq; Nourma Ulva Kumala Devi (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2025)
This study examines the polemics in implementing the Complete Systematic Land Registration Program (PTSL) in Tambelang Village, Krucil Sub-district, Probolinggo Regency, which has triggered land ownership disputes. Aimed at accelerating land certification and ensuring legal certainty, PTSL faces several field challenges, such as conflicting historical data, lack of public understanding, and alleged procedural abuse. Using a qualitative approach with a case study method, data were collected through interviews, observation, and document analysis. The findings indicate that weak data validation and insufficient public outreach often lead to new conflicts. The study recommends improving public communication, cost transparency, and optimizing mediation mechanisms to resolve land disputes. The results are expected to provide strategic input for local governments and the National Land Agency (BPN) to enhance future PTSL implementation.